2022
DOI: 10.1186/s12978-022-01508-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of completion of continuum of care in maternal health services on adverse birth outcomes in Northwestern Ethiopia: a prospective follow-up study

Abstract: Background Globally, around 4 million babies die within the first month of birth annually with more than 3 million stillbirths. Of them, 99% of newborn deaths and 98% of stillbirths occur in developing countries. Despite giving priority to maternal health services, adverse birth outcomes are still major public health problems in the study area. Hence, a continuum of care (CoC) is a core key strategy to overcome those challenges. The study conducted on the effectiveness of continuum of care in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…As a result, the final sample consisted of 823 pregnant women. However, this study was part of extensive research in which 2,402 pregnant women received follow-up care to determine the effects of a continuum of care in maternal health services on adverse birth outcomes ( 24 ), which was used as the final sample size for this study.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the final sample consisted of 823 pregnant women. However, this study was part of extensive research in which 2,402 pregnant women received follow-up care to determine the effects of a continuum of care in maternal health services on adverse birth outcomes ( 24 ), which was used as the final sample size for this study.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the maximum sample size calculated for this study was 719 newborns. Even though this study was part of large research work, the sample size was calculated for another objective found to be 2402 pregnant women [ 18 ]. After 11 months of follow-up and excluding abortion cases, the final sample size considered for this study was 2065 babies.…”
Section: Methodsmentioning
confidence: 99%
“…Sub-Saharan Africa alone accounted for approximately 70% of maternal deaths (202,000) [ 5 ]. Maintaining care from pregnancy to childbirth and during the postnatal period significantly reduces the unacceptably high rates of maternal and child mortality and morbidity [ 1 , 4 , 6 – 10 ]. This service offers a substantial opportunity to provide fully integrated care delivery, ensuring routine monitoring and a consistent opportunity for critical intervention throughout pregnancy, the crucial months post-delivery, and the entire postnatal period [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%